A Comparative Study of Thai Translations of “Shui Hu Zhuan” - Anantachote, Natthanya; Chen, Li (Journal of Sinology (วารสารจีนวิทยา), 2015)
Shui Hu Zhuan is one of the four most famous works of Chinese classical literature. It contains profound Chinese ethnic culture, historical background and social thinking. This thesis follows the pattern of six-step translation criticism proposed by Wang Hongyin, a Chinese translation theorist. From Peter Newmark’s semantic and communicative translation perspectives, this thesis performs a comparative and descriptive analysis of cultural terms. These words are selected from the two Thai translated versions — Somdet Chao Phraya Borom Maha Si Suriyawongse’s ซ้องกั๋ง and Charatchai Chiaoyut’s ซ้องกั๋งวีรบุรุษเขาเหลียงซาน. This thesis also examines how the translators of these two versions made their own adjustment and adaptation in translation.